Attacks on a Blind Signature-Based Steganographic Protocol of IEEE-WISP 2001 - Ling, Huo-Chong; Heng, Swee-Huay; Phan, Raphael C.-W. (2007)
We consider the security of a steganographic (or watermarking) protocol based on blind signatures proposed by Lenti et al. at WISP 2001. We remark that it is one that is a simple modification of existing blind signature schemes where the message to be signed blindly is replaced with an image to be watermarked. In this paper, we show that the trusted third party who signs the image blindly could be falsely led by an attacker to sign an image that is entirely different from the original. Besides, another well-known attack based on the multiplicative property of the RSA also applies here